DESAIN SISTEM INFORMASI LAYANAN KEUANGAN SEKOLAH BERBASIS CLOUD COMPUTING - Melda Agarina; Sutedi Sutedi; Arman Suryadi Karim (Institut Informatika dan Bisnis Darmajaya, 2018)
The financial services system is one that is important in the provision of education in college or also in school. Although education managers' understanding and awareness of the importance of an IT-based financial services system is increasing, there are still many educational institutions that do not yet have the capability to develop and implement IT-based financial services systems due to limited resources and funds. The development of cloud computing-based systems is a new paradigm in the IT world in delivering IT services that enable schools to implement IT-based service systems without having to invest in too large IT equipment. This study discusses the design of system architecture and the development of prototype software supporting school financial services. The results of this study are computer software that can be used to improve school financial services so as to help schools with limited resources and funds in the effort of developing the systemKeywords: Financial Service; Cloud Computing; IT Services.